Brand Loyalty Drivers of Indian Gen Z - Nilesh Gokhale, Ruby Chanda, Tajamul Islam (International Journal of Modern Agriculture, 2020)
Introduction: Born somewhere in mid-1990, Gen Z is estimated to be around 2 billion young people (Eva Heukäufer, Jane Cheung and Trevor Davis, July 2017) and be the largest segment of customers globally in coming years. Some studies about Gen Z have taken shape in western world and a very few have been done on Indian Gen Z. Marketers unanimously agree and realize that to market to each generation it is imperative to study their characteristics. Research Objectives: Brand loyalty is implicit in the attitude and the behavior of the customers regarding their willingness to repurchase the product and actual repurchase action (Chaudhuri and Holbrook, 2001). In dynamic technology market, brand value is largely based on mix of functional and social benefits offered by brand (Yeh et al. (2016). This study explores the Brand value dimensions and its relation with Brand Loyalty of Indian Generation Z in smart phones. Research Methodology: This is a cross-sectional exploratory research. The study includes a survey of Gen Z through a structured Questionnaire on a sample of 300 respondents in the state of Maharashtra. Scale items were adopted from Boakye et al. (2014), Sweeney and Soutar (2001), Tsai (2005), Sondoh et al. (2007). Factor analysis was employed to identify the underlying dimensions of brand loyalty of Generation Z using smart phones. Conclusion and Managerial implications: It highlights that for Gen Z, brand value comprises of functional dimensions (Functional Value-Quality and Functional Value-price) as well as affective dimensions (emotional value, social value). The results indicate that out of the above four dimensions of brand value; three have significant influence on brand loyalty. These three dimensions are Functional value (Quality), Social Value and Emotional value. The only non-significant dimension of Brand value was functional value price. This gives us enough basis to state that brand Loyalty of Gen Z is very significantly influenced by the affective dimensions and less by Functional dimension. Thus, marketers can drive brand loyalty among Gen Z by effectively formulating the strategy based on offering Quality, Emotional value and social value.